The analysis of risk, level of bank capital and bank performance: Evidence from Thailand - Lertbunditkul, Yuwarat (2019)
The objective of this study is to analyse the relationship between risk, the level of bank capital and bank performance of Thai banks. The panel data of nineteen Thai banks from 2011 to 2018 is applied to examine the relationship between the level of bank capital, risk and performance and the impact of bank capital on bank risk and profitability by carrying out the individual effects models. The empirical results illustrate that there is a significant negative relationship between the level of capital and bank risks, suggesting that capital is effective in reducing bank risks. Size also has a negative impact on bank risks, which contradicts “too big to fail” theory. Additionally, the level of capital is positively correlated to bank profitability, promoting an incentive for the banks to hold more capital. Another point is the bank efficiency variable; cost-to-income ratio presents a significant negative relationship to bank profitability. This research provides several benefits to the banks, regulators and the government to develop an appropriate regulatory policy.